Cross cultural adaptation, reliability and validity of the Greek version of Identification of Functional Ankle Instability (IdFAI) questionnaire. Issue 8 (December 2021) - Tsekoura, M.; Billis, E.; Samada, E.K.; Savvidou, I.; Fousekis, K.; Xergia, S.; Lampropoulou, S.; Tsepis, E.
Highlights: The IdFAI-GR questionnaire showed good psychometric performance. The IdFAI-GR is a reliable and valid questionnaire. The IdFAI-GR is available for use in future clinical research and practice. Abstract: Background: The objectives of our study were to develop the Greek version of the Identification of Functional Ankle Instability (IdFAI) questionnaire and to evaluate its psychometric properties. Methods: The IdFAI was translated and adapted into Greek according to the guidelines for cross-cultural adaptation of self report measures. It was tested for test-retest reliability, validity, internal consistency and floor-ceiling effects in 141 participants (54 males, 87 females; 23.5 ± 7.2 years). All participants were asked to fill the Greek IdFAI (IdFAI-GR), the Cumberland Ankle Instability Tool (CAIT), and the Lower Extremity Functional Scale (LEFS), in order to determine construct validity. To determine the test-retest reliability, fifty randomly selected individuals re-filled IdFAI seven days after the first session. Results: The IdFAI-GR had high internal consistency (Cronbach alpha = 0.94) and excellent test-retest reliability (ICC2, 1 = 0.97; SEM = 0.7). The IdFAI-GR had strong correlation with the CAIT (r = 0.7; p < 0.001) and moderate correlation with the LEFS (r = 0.5; p < 0.001). No ceiling or floor effects were observed. Conclusion: The Greek IdFAI questionnaire has proven to be a valid and reliable instrument to identify functional ankle instability. It can therefore, be used for both clinical and research purposes in Greek-speaking individuals.